Moringa oleifera extract and rutin prevent monosodium glutamate-induced nephrotoxicity in rats - Doaa M. Abdel-Aty; Sherif R. Mohamed; Wafa A. Al-Megrin; Nashmiah Sindi Alshammari; Mohammed M. Althaqafi; Ali H. Alghamdi; Rami B. Kassab; Mona A. Ibrahim; Ahmed E. Abdel Moneim; Doaa Soliman; Ayah S. Fathalla (Journal of Agriculture and Food Research)
Monosodium glutamate (MSG) is widely used as a flavor enhancer but has been associated with adverse effects. This study evaluated the protective effects of Moringa oleifera (MO) extract and rutin against MSG-induced renal damage in rats. Sixty adult male rats were randomly divided into six groups (n = 10/group): control, MSG (60 mg/kg), MO extract (500 mg/kg), rutin (150 mg/kg, MO + MSG, and rutin + MSG. All treatments were administered via oral gavage once daily for 30 days. Oral administration of MSG led to a significant increase in body weight (by 14.67 %), kidney weight (by 41.16 %), and relative kidney weight (by 22.76 %). MSG oral administration significantly increased serum uric acid (by 94.702 %), urea (by 46.273 %), and creatinine (by 80.345 %) compared to controls. In renal tissue, MSG increased malondialdehyde (by 40.892 %) and nitric oxide (by 42.176 %) levels while decreasing glutathione (by −38.730 %) and antioxidant enzyme activities including superoxide dismutase (by −28.485 %), catalase (by −18.158 %), glutathione peroxidase (by −29.862 %), and glutathione reductase (by −35.628 %). MSG also elevated pro-inflammatory markers interleukin-1β (by 83.411 %) and tumor necrosis factor-α (by 40.524 %), and enhanced cyclo-oxygenase-2 activity (by 454.294 %). Histopathological examination revealed MSG-induced glomerular damage, tubular degeneration, and interstitial inflammation. Administration of MO extract or rutin before MSG significantly ameliorated these changes, with MO extract showing slightly superior effects in most parameters. MO extract reduced serum creatinine by −28.294 % and urea by −20.625 %, while rutin achieved −32.493 % and −29.691 % reductions respectively. Both treatments normalized oxidative stress markers and inflammatory mediators to near-control levels. Histological analysis confirmed their protective effects through preserved renal architecture and reduced inflammatory infiltration. These findings demonstrate that both MO extract and rutin protect against MSG-induced nephrotoxicity through antioxidant and anti-inflammatory mechanisms, with quantifiable improvements in biochemical, immunohistochemical, and histological parameters.